Penerapan Metode Ahp Dalam Penilaian Kinerja Dosen Pada Universitas Muhammadiyah Bengkulu - Maringga, Gleichenia; Juansen, Monsya; Gunawan, Gunawan; Erwadi, Yetman (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Lecturer performance evaluation is a crucial part of efforts to improve the quality of higher education. However, the wvaluation process often encounters challenges such as subjectivity and inconsistency in determining the weight of each criterion. This study aims to design an objective, systematic, and measurable lecturer performance assessment modal using the Analytical Hierarchy Process (AHP) method at Universitas Muhammadiyah Bengkulu. The AHP process wa carried out thraugh pairwise comparisons to obtain priority weights, followed by a consistency check with a consistent rasio (CR) of (0.04), indicating that the evaluation was valid and consistent. The results show that the criteria of Teaching and Learning and Research have the highest weights (0.29), making them the most dominant aspects of the evaluation. The sub-criterion “Developing Teaching Materials” hold the highest global weight (142.70), highlighting the importance of innovation in learning materials. Out of 20 lecturers evaluated, Lecturer 7 achieved the highest performance score (87.5526). This study concludes that AHP can serve as an effective decision support tool in lecturer performance evaluation systems and can be used as a reference in developing a more fair and transparent assessment model.